The Effect Of Quantum Teaching Learning Model To Enhance Students’ Conceptual Understanding on Characteristic Material Concept - Ravita Dewi; Mahmud Alpusari; Lazim N (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2018)
This research aims to investigate effect of quantum teaching learning model toenhance students’ conceptual understanding on characteristic material concept.This study method was experiment with quasy experiment. Subject this researchwas fifth grade elementary school. Result of this study found significant score0,000 < 0,05. It is mean that hypothesis of research was accepted. It can beconcluded Quantum Teaching learning model can improve students’ conceptualunderstanding.